Repairing modern composite dental fillings - Salamonowicz, Małgorzata; Choromańska, Magdalena (Journal of Stomatology, 2017)
Introduction. Despite the development of dentistry materials science, modern composite fillings still fail to provide a solution for life and become damaged relatively often. Therefore, to save tooth tissues, the procedure of composite filling repair has become popular as an alternative to complete replacement. So far, no uniform method has been developed for the reparative procedure, and the variety of materials makes the selection of the right procedure difficult. Aim of the study. This paper is aimed at finding a universal repair procedure by reviewing contemporary literature on the subject. Material and methods. Pubmed database have been reviewed in order to find the literature concerning some research associated with dental composite restoration. The following key words have been used: “dental composite”, “resin composite”, “restoration”, “dental filling”, ”repair”, “renovation”, ” repair bond strength”. Enclosure criteria were: original and review papers, published after 2012, written in English. Articles concerning information about repair of no resin composite dental filling have been excluded. Results. Research including various aspects of dental composite repair have been enclosed to the review to facilitate clinicians undertake right decisions in different conditions Conclusion. In modern trend of minimally invasive dentistry repairing composite dental fillings instead of its replacement is widespread procedure that still don’t have ready procedure scheme. These paper focuses on finding these universal procedure. Despite all its advantages, composite filling repair is not a simple procedure.